.Antiparasitic activities of two sesquiterpenic lactones isolated from Acanthospermum hispidum D.C. - GBAGUIDI, A. (My University, 2012)
Ethnopharmacological relevance: Aerial parts of Acanthospermum hispidum D.C. are often used by traditional healers in Benin for various diseases and especially for malaria. Aim of the study: To identify active compounds from extracts of Acanthospermum hispidum D.CV. leaves previously shown to possess antimalarial properties and analyse in vivo activity and toxicity of crude extracts. Materials and methods: Compounds were isolated from aerial part of Acanthospermum hispidum D.C. and structurally elucidated using extensive spectroscopic analysis. Antiplasmodial activity was evaluated in vitro against a chloroquine-sensitive strain of Plasmodium falciparum (3D7) using the measurement of the plasmodial lactate dehydrogenase activity and in vivo against Plasmodium berghei berghei by the 4-day suppressive test. Selectivity of extract and purified compounds on Plasmodium parasites were evaluated by using MTT test on J774 macrophage like murine cells and WI38 human normal fibroblasts and also against two other parasites: Trypanosoma brucei brucei and Leishmania mexicana mexicana. Acute and sub-acute toxicities of a crude extract were evaluated on mice. Results: Two known sesquiterpenic lactones were isolated: 1 (15-acetoxy-8β-[(2-methylbutyryloxy)]-14-oxo-4,5-cis-acanthospermolide) and 2 (9α-acetoxy-15-hydroxy-8β-(2-methylbutyryloxy)-14-oxo-4,5-trans-acanthospermolide). 1 and 2 showed in vitro antiplasmodial activity against the chloroquine-sensitive strain (3D7) with IC(50) of 2.9±0.5 and 2.23±0.09μM respectively. Only 2 showed a high selectivity index (SI: 18.4) on Plasmodium compared to cytotoxicity against human fibroblasts cell line (WI38). 1 and 2 also showed interesting antiparasitic activities in vitro against Trypanosoma brucei brucei (IC(50) of 2.45±0.49 and 6.36±1.42μM respectively) and Leishmania mexicana mexicana (IC(50) of 0.94±0.05 and 2.54±0.19μM respectively). Furthermore, crude acidic water extract and fractions containing one of the two isolated compounds displayed a weak in vivo antimalarial activity against Plasmodium berghei berghei with a long half-life causing a delayed effect. In vivo acute (2000mg/kg) and sub-acute (1000mg/kg) toxicity tests on the crude acidic water extract did not show toxicity. Conclusion: Crude acidic water extract, fractions and pure isolated compounds from Acanthospermum hispidum showed promising in vitro antiplasmodial activity. Despite our study did not show in vivo acute and subacute toxicities of the crude acidic water extract, its weak in vivo antimalarial activity and the in vitro cytotoxicity of pure compounds and enriched extracts containing 1 and 2 indicate that the aerial parts of Acanthospermum hispidum should be used with caution for malaria treatments.